Flipped Learning Model Based on Learning Styles in Chemıstry Educatıon - Karapınar, Sema; Kadıoğlu, Nagihan; Özyalçın Oskay, Özge (SCAD Independent, 2023)
This study aimed to investigate the effectiveness of the flipped learning model, which was designed according to learning styles in the unit of